Design for reliability - Raheja, Dev; Gullo, Louis J. (Wiley, 2012)
"The aim of Design for Reliability (DFR) is to design for zero failures of critical system functions, which results in enormous savings in life cycle costs for producers and users. This practical guide helps readers to understand the best-of-breed methods, technologies, and tools for incorporating reliability into the complex systems design process. A significant feature of the book is the integration of ideas from computer science and market engineering. By adopting these design principles and learning from "insight" panels, engineers and managers will improve their ability to compete in global markets".